ROLE OF PLATELET INDICES IN DENGUE FEVER CASES IN CORRELATION WITH SEROLOGICAL MARKERS – A STUDY OF 100 CASES - k, srikanth reddy; V, Bharadwaj; Naidu, Sree Ramulu (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study aims to evaluate the utility of various platelet indices, i.e., platelet count, mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT) in dengue fever and to study different serological markers (NS1 Ag, IgM, and IgG) and compare them with platelet counts. Methods: This was a retrospective, observational, and cross-sectional study done over 6 months. A total of 100 cases with symptoms of dengue and seropositive for any of the rapid tests (NS1 Ag, Ig M, and Ig G antibodies) were included. Platelet count, MPV, (PDW), and (PCT) were determined using six-part Hematology analyzer. Based on the platelet count, all dengue seropositive cases were divided into 5 groups, and platelet indices were analyzed and tested for statistical significance using Chi-square test and Anova test. Results: Thrombocytopenia was more common in the NS1 Ag-only reactive cases. Dengue hemorrhagic fever (DHF) cases (12) had significantly low MPV, high PDW, and low PCT. Statistical analysis between mean MPV, mean PDW, mean PCT, and platelet count among various groups was significant. Low MPV, high PDW, and low PCT were more evident when platelet count was < 1lakh. Conclusion: Our study showed that thrombocytopenia was more common in the NS1 Ag-only reactive cases than other serological markers.A Low MPV with a spike in PDW, and a plummeted PCT in cases with thrombocytopenia indicate severity of dengue infection. These platelet indices act as surrogate markers in predicting the risk of bleeding.